Linear IgA bullous disease with possible immunoreactivity to the basement membrane zone and dermal blood vessels - Ana Maria Abreu Velez; Vickie M. Brown; Michael S. Howard (Our Dermatology Online, 2014)
Introduction: Linear IgA bullous dermatosis (LAD) is an immunobullous disorder, in which IgA antibodies are deposited along the basement membrane zone (BMZ) of the skin in a linear pattern. The cause of this disease is unknown, but the eruption may occur more commonly in association with certain medications. Case report: A 61 year old woman presented with blisters in the axillae and legs, with pain, itching and swelling. She was taking many medications for other conditions such diabetes and obesity. Tense blisters were seen, primarily on the legs and accompanied by some ankle swelling. Methods: Skin biopsies for hematoxylin and eosin (H&E) examination, as well as for direct immunofluorescence (DIF), and immunohistochemistry (IHC) studies were performed. Results: The H&E examination revealed a subepidermal blister, with small numbers of lymphocytes, neutrophils and eosinophils noted within the blister lumen. The dermis also displayed a mild, superficial, perivascular infiltrate of lymphocytes and histiocytes; eosinophils and neutrophils were also noted. DIF and IHC studies confirmed the diagnosis of linear IgA (LAD) at the BMZ. However, in addition to immunoglobulin A, we also observed deposits of IgA, IgM, IgG, IgD, Kappa, Lambda, Complement/C3c, C1q, fibrinogen and albumin around upper dermal blood vessels. Conclusions: LAD has been most commonly associated with medication intake; the most common DIF immune response is the presence of linear IgA at the BMZ. However, here we found additional reactivity to against dermal blood vessels. Because the patient is affected by diabetes mellitus, it is difficult to know if the observed vascular reactivity was associated with the diabetes or solely an immune reaction to the vessels. Based on our findings, we encourage searching for vascular reactivity in cases of LAD.